Do recurso ao cravo no século XX em óperas de Ruy Coelho, Augusto Machado e Joly Braga Santos - Ayres de Abreu, Edward (2021)
When Ruy Coelho (1889-1986), possibly influenced by Wanda Landowska, included the harpsichord in the orchestration of his first opera, he became the first modern Portuguese composer to resort to this previously forgotten instrument. He would go on to use it in several other works, and would be one of few within the Portuguese musical milieu to do so. This paper seeks to reflect on the conceptual and musical background to this revival of the harpsichord, the associated technical and organologic obstacles, and ultimately the instrument’s raison d’être and significance in the dramatic and musical context of 20th-century Portuguese operas Serão da infanta (1913) and Rosas de todo o anno (1921) by Ruy Coelho, Rosas de todo o anno (1920) by Augusto Machado (1845-1924) and Trilogia das Barcas (1970) by Joly Braga Santos (1924-1988).